Peran Humas Sekretariat DPRD Kota Palembang Dalam Menyampaikan Informasi Publik - Haniyah Eva Yuniar; Achmad Syarifudin; Muslimin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2023)
This study discusses the Role of Public Relations of the Palembang City DPRD Secretariat in Conveying Public Information. This study aims to determine how the role of public relations secretariat DPRD Palembang City in conveying public information, the function of public relations secretariat DPRD Palembang City in conveying public information, obstacles in conveying public information. The theory used in this research is the theory of public relations according to Dozier and Broom. The research method used is descriptive qualitative research. The sources of research informants in this study were the Head of Public Relations of the Palembang City DPRD Secretariat, and the Public Relations staff of the Palembang City DPRD Secretariat. Data collection techniques are using observation, interviews, and documentation. The data analysis technique used by Miles and Huberman. The results of the study show that (1) the role of Public Relations of the Palembang City DPRD Secretariat in Delivering Public Information Public Relations As a communication facilitator which means that public relations has a role to hear complaints from the public who are accommodated by public relations and then conveyed to leaders, both public relations as problem-solving facilitators which means public relations will seek solutions to the problems faced by the palembang city government, the three public relations as a communication technique so that public relations know whether there is reciprocity between the government and the community so that it is profitable for the government. to the media crew. (3) The obstacle to Public Relations of the Palembang City DPRD Secretariat in conveying public information is the lack of Human Resources (HR) owned by the Public Relations of the Palembang City DPRD Secretariat. because not all public relations staff have a scientific background majoring in communication science or related to journalism so that it becomes an obstacle when public relations deals with the media or journalists. In addition, there are internet network disturbances. When public relations perform their duties out of town, but there is sudden information. However, for this problem the Public Relations of the Palembang City DPRD Secretariat can overcome it.